Generation dead - Waters, Daniel, 1969- (New York : Hyperion, 2008)
When dead teenagers who have come back to life start showing up at her high school, Phoebe, a goth girl, becomes interested in the phenomenon, and when she starts dating a "living impaired" boy, they encounter prejudice, fear, and hatred.
820
Accelerated Reader AR
A Junior Library Guild selection.
Keywords: Death -- Fiction; High schools -- Fiction; Interpersonal relations -- Fiction; Prejudices -- Fiction; Schools -- Fiction; Zombies -- Fiction